(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Studied in low doses of benzimidazole drugs 0.5 mg/g, an increase in seedling growth of up to 136% was observed in the tested cotton crops. Relatively high stimulation of the number of lateral roots provided by the Hib drug on cotton is up to 178%. The same drugs in higher doses of 25 mg/l suppress seed germination and inhibit growth processes. In laboratory conditions, when administered in low doses, the drugs have a positive effect on the content of green pigments in cotton.